Preparatory acoustic emission activity of hydraulic fracture in granite with various viscous fluids revealed by deep learning technique. Issue 1 (9th March 2021) - Tanaka, Rui; Naoi, Makoto; Chen, Youqing; Yamamoto, Kazune; Imakita, Keiichi; Tsutsumi, Naofumi; Shimoda, Akihiro; Hiramatsu, Daiki; Kawakata, Hironori; Ishida, Tsuyoshi; Fukuyama, Eiichi; Tanaka, Hiroyuki; et al.
SUMMARY: To investigate the influence of fluid viscosity on the fracturing process, we conducted hydraulic fracturing experiments on Kurokami-jima granite specimens with resins of various viscosities. We monitored the acoustic emission (AE) activity during fracturing and estimated the moment tensor (MT) solutions for 54 727 AE events using a deep learning technique. We observed the breakdown at 14–22 MPa of borehole pressure, which was dependent on the viscosity, as well as two preparatory phases accompanying the expansion of AE-active regions. The first expansion phase typically began at 10–30 per cent of the breakdown pressure, where AEs occurred three-dimensionally surrounding the wellbore and their active region expanded with time towards the external boundaries of the specimen. The MT solutions of these AEs corresponded to crack-opening (tensile) events in various orientations. The second expansion phase began at 90–99 per cent of the breakdown pressure. During this phase, a new planar AE distribution emerged from the borehole and expanded along the maximum compression axis, and the focal mechanisms of these AEs corresponded to the tensile events on the AE-delineating plane. We interpreted that the first phase was induced by fluid penetration into pre-existing microcracks, such as grain boundaries, and the second phase corresponded to the main fracture formation. Significant dependences on fluid viscosity were observed in the borehole pressure at the time of main fracture initiation and in the speed of the fracture propagation in the second phase. The AE activity observed in the present study was fairly complex compared to that observed in previous experiments conducted on tight shale samples. This difference indicates the importance of the interaction between the fracturing fluid and pre-existing microcracks in the fracturing process.